ANALISIS PERSEBARAN KECELAKAAN LALU LINTAS JALAN RAYA DI KOTA JAMBI (STUDI KASUS JALAN ARTERI PRIMER) - Mega Nurhidayanti; Arie Yulfa (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
ABSTRACT This study aims to (1) determine the characteristics and location of traffic accident-prone areas in the city of Jambi, (2) analyze the location of accident-prone areas and (3) find out the efforts of the police, especially the Polresta Jambi in reducing accident rates. The source of this research is the jambi polresta traffic accident report from 2014-2018. Then the accident rate is calculated using the Accident Equivalent Number method and analyzed in order to get an accident-prone location using the Upper Control Limit method. The results of this study indicate that the road identified as an accident-prone area is the South Ring Road, West Ring Road and Surya Dharma Road segments because it has an EAN accident number exceeding UCL, where on Jl. South Circle EAN = 648, UCL = 285, Jl. West Circle EAN = 447, UCL = 278 and Jl. Surya Dharma EAN = 363, UCL = 274. Material losses due to traffic accidents from 2014-2018 reached Rp. 2,032,555,000. The characteristics that occur are, when the accident is vulnerable to occur on Business Day (71%) between 12.00-18.00 WIB (33%). The highest type of collision is the position of hit-and-run (39%). The highest number of vehicles involved in accidents was double (85%). The most types of accident victims were minor injuries (88%). Based on the efforts of the police, especially members of the Jambi Police in reducing the number of accidents, do patrols, reprimands and actions if the mistakes are cannot be fixed and appeal to various places every day.